Air flow temperature measurements using infrared thermography. Issue 1 (2nd January 2017) - Vinnichenko, Nikolay; Plaksina, Yulia; Yakimchuk, Olga; Soldatenkova, Ksenia; Uvarov, Alexander
Abstract: Accuracy of two infrared thermography techniques for air flow temperature measurements is evaluated for a benchmark test case of natural convection over a horizontal heated plate. The first technique, which can be called infrared thermography of optically thin media, involves observation of a distant screen with known temperature through the investigated air flow. It allows obtaining 2D temperature fields averaged along line-of-sight, like quantitative schlieren or interferometry techniques, using only software supplied with infrared camera. The second technique employs solid targets installed within the air flow. Temperature distributions, obtained with both methods, are compared to each other, to measurements using background oriented schlieren technique, to thermocouple measurements and to results of 2D and 3D numerical simulations. It is shown that solid target apparent temperature is affected by radiative heat exchange with environment, in this particular case with the heated plate. Simultaneous use of three kinds of targets with special treatment is proposed to take this effect into account. Infrared thermography of optically thin media is shown to be simple and reliable non-intrusive technique for air flow temperature measurements with random error increasing with transmissivity of the flow under study.